2009
DOI: 10.1377/hlthaff.28.2.w251
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Outcomes And Efficiency In Medicare Value-Based Purchasing

Abstract: The Medicare program may soon adopt value-based purchasing (VBP), in which hospitals could receive incentives that are conditional on meeting specified performance objectives. The authors advocate for a market-oriented framework and direct measures of system-level value that are focused on better outcomes and lower total cost of care. They present a multidimensional framework for measuring outcomes of care and a method to adjust incentive payments based on efficiency. Incremental reforms based on VBP could pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…17 Concurrently, the Centers for Medicare and Medicaid Services are implementing a value-based purchasing program that starts with a 5% withhold in reimbursement that institutions need to earn back through a combination of mortality, process, and patient satisfaction metrics. 18 The administration also reserved $19 billion to promote improvement of health IT for American medicine. 19 Using health IT investment to help hospitals is an appealing concept, but for many institutions the infrastructure required to make that transition directly competes with other patient needs, including bedside patient care.…”
Section: A Possible Stimulus: Investing In Quality Initiatives At Fismentioning
confidence: 99%
“…17 Concurrently, the Centers for Medicare and Medicaid Services are implementing a value-based purchasing program that starts with a 5% withhold in reimbursement that institutions need to earn back through a combination of mortality, process, and patient satisfaction metrics. 18 The administration also reserved $19 billion to promote improvement of health IT for American medicine. 19 Using health IT investment to help hospitals is an appealing concept, but for many institutions the infrastructure required to make that transition directly competes with other patient needs, including bedside patient care.…”
Section: A Possible Stimulus: Investing In Quality Initiatives At Fismentioning
confidence: 99%
“…The study identified 7 dimensions for the HVBP model and 33 components. As the results of the study showed, an important dimension for the identified model was quality of clinical care that included the components or measures such as acute myocardial infarction (AMI), heart failure (HF), pneumonia (PN), surgical care improvement project (SCIP), and Healthcare Associated infections (HAI), similar to the HVBP model in the US (18,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The HVBP is computed using the following four dimensions (9,18,34,37,47,48): -Efficiency (E) In the US model of HVBP, the weights of the HVBP dimensions are expressed in terms of TPS (4,18,37,48). TPS in VBP is calculated based on four dimensions including quality of clinical care 20%, patient experience 30%, outcome 30%, and efficiency 20% of TPS in 2016 -2017 (18,37,(48)(49)(50):…”
Section: Discussionmentioning
confidence: 99%
“…11 The IOM report provided momentum to legislatively mandate "pay for performance," prompting the emergence of new programs. 12 One of these, the Physician Quality Reporting System (PQRS), was established as the Physician Quality Reporting Initiative under the 2006 Tax Relief and Health Care Act (TRHCA), based on the notion that health care providers should be able to provide quality and outcome information not otherwise readily available from existing Medicare claims. 13 Early data suggested limited eligible provider participation.…”
Section: Selected Historymentioning
confidence: 99%